A Bibliometric Analysis of Green Financing and Renewable Energy Research for 2000-2023 - Uwuigbe, Uwalomwa; Eluyela, Damilola Felix; Martins, Bankole Olajide; Uwuigbe, Olubukola Ranti; Musa, Saidu (International Journal of Energy Economics and Policy, 2024)
This bibliometric analysis examines the research on green financing and renewable energy from 2000 to 2023. ​The study analyses the publication trends, most productive countries and institutions, frequently occurring concepts, and active and cited authors in this field. The findings reveal a significant increase in publications on green financing and renewable energy in recent years which highlights the increasing interest and investment in these fields, with China being the most productive country. The analysis of keywords highlights the focus on renewable energy, sustainability, and climate change. ​ The study also identifies the most active and cited authors, as well as the top journals in this research area. Overall, the analysis underscores the growing interest and importance of green financing and renewable energy in addressing climate change and promoting sustainable development. ​The analysis presents future opportunities for research in the areas of green financing and renewable energy, as well as the development of sustainable finance and renewable energy solutions.